2006
DOI: 10.1103/physrevlett.96.141301
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Nature of the Big Bang

Abstract: Some long-standing issues concerning the quantum nature of the big bang are resolved in the context of homogeneous isotropic models with a scalar field. Specifically, the known results on the resolution of the big-bang singularity in loop quantum cosmology are significantly extended as follows: (i) the scalar field is shown to serve as an internal clock, thereby providing a detailed realization of the "emergent time" idea; (ii) the physical Hilbert space, Dirac observables, and semiclassical states are constru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
1,306
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 787 publications
(1,338 citation statements)
references
References 17 publications
28
1,306
2
2
Order By: Relevance
“…However, an effective Hamiltonian description on a continuum spacetime can be constructed by using semiclassical states, which has been shown to very well approximate the quantum dynamics [13,14]. This analysis reveals that on backward evolution of our expanding phase of the universe, the universe bounces at a critical density (near the big bang singularity) into a contracting branch [12,18]. Thus the classical singular problem can be successfully overcome within the context of LQC by a nonsingular bounce.…”
Section: Effective Dynamics In Loop Quantum Cosmology and Big Bounce mentioning
confidence: 99%
See 1 more Smart Citation
“…However, an effective Hamiltonian description on a continuum spacetime can be constructed by using semiclassical states, which has been shown to very well approximate the quantum dynamics [13,14]. This analysis reveals that on backward evolution of our expanding phase of the universe, the universe bounces at a critical density (near the big bang singularity) into a contracting branch [12,18]. Thus the classical singular problem can be successfully overcome within the context of LQC by a nonsingular bounce.…”
Section: Effective Dynamics In Loop Quantum Cosmology and Big Bounce mentioning
confidence: 99%
“…Within the framework of LQC, some long-standing issues concerning the quantum nature of the big-bang are resolved in the context of homogeneous and isotropic universe with a scalar field. Using extensive analytical and numerical methods, the analysis of the evolution of the semiclassical states for a spatially flat universe has shown that the universe has a pre-big-bang branch, joined deterministically to the post-big-bang branch by a quantum bounce in the deep Planck regime through the LQC evolution [12,13,14]. Thanks to the nonperturbative background independent methods of LQC, the idea of the nonsingular bounce can be realized in a natural fashion.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been successfully quantized in LQC and its physics has been well understood [4]. The underlying quantum constraint is non-local and uniformly discrete in volume.…”
mentioning
confidence: 99%
“…In recent years, extensive analytical work and numerical simulations have shown that the big bang singularity can be resolved in LQC. The non-perturbative quantum geometric effects result in a quantum bounce to a pre-big bang branch when the energy density of the universe reaches close to the Planck scale [4]. Further, analysis from exactly solvable models show that the bounce is generic [5].…”
mentioning
confidence: 99%
“…Loop quantisation of the homogeneous and isotropic FRW models have been performed in Ref. [3,4,5] (K = 0), Ref. [6,7] (K = 1) and Ref.…”
Section: Introductionmentioning
confidence: 99%